Instagram for peer teaching: opportunity and challenge. Issue 6 (1st November 2020) - Gulati, Radhika Rani; Reid, Helen; Gill, Mandeep
ABSTRACT: Medical education is increasingly being delivered beyond the boundaries of the classroom. Online learning and peer teaching are particularly popular among educators to complement traditional, didactic teaching methods. In light of the COVID-19 pandemic, students at the Queen's University Belfast's (QUB) General Practice Society started creating daily multiple-choice questions (MCQs) on Instagram to help continue learning while placements were suspended. There were high levels of engagement with the MCQs, with students reporting the content to be both relevant and useful for their learning. The project also allowed us to gain early experience of teaching, furthered our own learning and helped develop key skills (e.g. providing constructive feedback, creativity, self-directed learning) important for both our professional and personal development. Nonetheless, there are few published examples of the use of Instagram within medical education. Further work needs to be carried out to summarise projects delivered on the platform, train educators in using Instagram, and encourage students to get involved in finding further, novel methods of delivering medical education.